Stochastic flow and noise associated with the Tanaka stochastic differential equation - Watanabe, S. (Український математичний журнал, 2000)
We study the properties of the noise (in the Tsirelson sense) that is generated by the solutions of the well-known Tanaka equation. Досліджуються властивості шуму (в розумінні Б. Цірельсона), який породжується розв'язками відомого рівняння Танаки.